2001
DOI: 10.1074/jbc.m106408200
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetosome-specific GTPase from the Magnetic BacteriumMagnetospirillum magneticum AMB-1

Abstract: Magnetic bacteria produce intracellular vesicles that envelope single domain magnetite crystals. Although many proteins are present in this intracellular vesicle membrane, five are specific to this membrane. A 16-kDa protein, designated Mms16, is the most abundant of the magnetosome-specific proteins, and to establish its function we cloned and sequenced its gene from Magnetospirillum magneticum AMB-1. This was achieved by determination of the N-terminal amino acid sequence of the protein following two dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 52 publications
0
78
1
Order By: Relevance
“…This sensing and regulatory module is flanked by the upregulated genes Rru_A3284 and Rru_A3283 encoding for, respectively, a putative molecular chaperone for exported proteins and a GTPase. The latter is similar to the small GTPases involved in the formation of intracellular vesicles in magnetic bacteria (Okamura et al 2001) and could also stabilize the protein transport-related SecA protein (Rru_A0235) (Mü ller et al 1992), which was upregulated 1.8-fold (Po0.05).…”
Section: Message 2 and Related Experimentsmentioning
confidence: 95%
“…This sensing and regulatory module is flanked by the upregulated genes Rru_A3284 and Rru_A3283 encoding for, respectively, a putative molecular chaperone for exported proteins and a GTPase. The latter is similar to the small GTPases involved in the formation of intracellular vesicles in magnetic bacteria (Okamura et al 2001) and could also stabilize the protein transport-related SecA protein (Rru_A0235) (Mü ller et al 1992), which was upregulated 1.8-fold (Po0.05).…”
Section: Message 2 and Related Experimentsmentioning
confidence: 95%
“…However, MagA maintains a large hydrophobic domain, which renders it unsuitable for assembling membrane proteins. Mms16 was found to be a smaller protein that was abundantly expressed in the BacMP membrane (Okamura et al 2001). It is tightly anchored in the membrane by myristoylation.…”
Section: Protein Assembly On the Surface Of Magnetic Particlesmentioning
confidence: 99%
“…They investigated the precise localization of Mam22 and Mam12 (identical to Mms13 and MamC) and revealed that Mam22 and Mam12 exist in the matrix and the BacMP membrane, respectively. A 16 kDa protein (Mms16), a small GTPase, is speculated to prime the invagination of the cytoplasmic membrane for vesicle formation in M. magneticum AMB-1 (Okamura et al 2001). MpsA shows homology with acetyl-CoA carboxylase (transferase) and the acyl-CoA-binding motif, which is considered to function as a mediator of cytoplasmic membrane invagination (Matsunaga et al 2000b).…”
Section: Protein Analyses Of the Bacmp Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular studies have postulated the steps of BMP synthesis (7)(8)(9). Several proteins located on or in the BMP membrane have been isolated and analyzed in Magnetospirillum magneticum strain AMB-1.…”
mentioning
confidence: 99%